High-order thinking skill (HOTS) of the students in aspect of understanding modern poetry and prose of Malay language - Jamian, Abdul Rasid; Wan Jaafar, Wan Nazira; Othman, Shamsudin; Md Sabil, Azhar (Human Resource Management Academic Research Society, 2018)
This study aimed to evaluate high order thinking skill (HOTS) proficiency of students in the understanding of poetry and prose of modern Malay. The samples were carried out in this study were 210 students using quantitative methods as the study design. The findings showed that HOTS for understanding poetry is moderate (mean=2.35, SD=1:07), while the understanding of modern prose is at a high level (mean=2.67, SD=0.98). There are no significant differences between gender in the understanding of modern poetry, but there are significant differences between female students (mean=2.83, SD=0.91) and boys (mean=2.47, SD=1.03) in the understanding of modern prose. Significant differences between the level of HOTS in terms of understanding the poem (mean=3.38, SD=0.64), prose (mean=3.13, SD=0.54) as well as modern poetry and prose (mean=3.25, SD=0.49) among students of high level, medium and low can also be seen. In conclusion, the HOTS should be mastered by students not only academically but also non-academically and the practice of applying HOTS in them through appropriate teaching methods can improve their performance in their studies.